Kajian Analisis Struktur Bahasa Tingkat Dasar pada Slogan Reklame di Kabupaten Rejang Lebong - Ifnaldi Ifnaldi; Sinta Sintiani (AR-RIAYAH: Jurnal Pendidikan Dasar)
Advertising sentences are written in good language, easy to understand and with the right language structure. The purpose of this study was to determine how the use of language structure in writing in advertisements and forms of typos in the Indonesian Spelling Guidelines (PUEBI) contained in these advertisements. This type of research is field research with a descriptive qualitative approach (Field Research), data collection is carried out through observation, documentation and recording methods, the results of the study reveal that the use of language structures on billboards and typos is: (1) 4 language structures The billboards encountered by the author are evocative, informative, persuasive and effective. Where the use of evocative language reached 18.9%, informative 61.1%, persuasive 15.6% and kinetic energy 4.4%. Although there are errors in the use of punctuation marks such as commas, (,) and letters.